(untitled) - Gear, Jolene (Cambridge, 2006)
A new edition designed to prepare students for the TOEFL® iBT test, administered online. Cambridge Preparation for the TOEFL® test, Fourth Edition helps students master the language skills they need to succeed on the TOEFL® iBT Test and communicate effectively in an academic setting. Using an integrated skills approach that mirrors the structure of the TOEFL® iBT, this fully revised text is ideal for classroom use and self-study. The book contains hundreds of skill-building exercises covering all of the question types in the exam and four practice tests. A supporting skills section is provided to improve grammar, vocabulary, pronunciation and study skills. The CD-ROM presents the book tests and three additional practice tests in an electronic format that simulates the online TOEFL® iBT test. The audio program available on audio CD or audio cassette contains conversations and lectures for all listening exercises and test questions.
Keywords: English language,English language,Test of English as a foreign language; Examinations